Key elements of real estate agency websites – analysis of the customer preferences with use of the Kano method - doi.org/10.17512/bozpe.2025.14.01; Katarína Lestyánszka Škůrková (Budownictwo o Zoptymalizowanym Potencjale Energetycznym)
The real estate sales market is highly competitive, particularly in the residential sector. In 2024, Poland experienced a slight increase in property sales, reflected in a 5 % rise in prices. The decision to search for or purchase a property depends on numerous factors. One key factor is the work of real estate agencies and agents, who assist both buyers and sellers throughout the process. A wealth of information regarding specific properties, as well as the buying and selling process, can be found on real estate agency websites. This article aims to analyze the preferences of potential customers regarding the functionality and content of these websites. The Kano method was used in the study to identify which types of information are considered essential by potential customers and which factors influence their decision to choose one agency over another. The findings provide real estate agencies with valuable insights to improve and optimize their websites.